STATE AND ASSESSMENT OF THE EFFICIENCY OF COST MANAGEMENT OF INDUSTRIAL ENTERPRISES - IVANOV, Maxim (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The processes of forming market relations in Ukraine require profound changes in the cost management methods of industrial enterprises. The need to use modern market performance criteria is increasing, and the requirements for management flexibility are increasing. The main guideline and measure of the success of the enterprise is the amount of profit. At the same time, the problem of cost-effective formation is in many cases receiving insufficient attention. In this regard, the modern stage of development of domestic industrial enterprises is largely characterized by spontaneity and unpredictability of the processes of formation of production costs. They need more attention to the interconnections and interdependencies of the various activities and management functions in generating production costs, including rationing, planning, accounting, and analysis. Existing deficiencies in cost management lead to an imbalance in the whole process of their formation, and as a result, to excess costs, which can be prevented in the rational organization of the process. This resulted in an excessively high level of costs for a number of domestic enterprises compared to similar enterprises in developed countries.The processes of formation of market relations in Ukraine require deep transformations in the cost management methods of industrial enterprises. The need to use modern market efficiency criteria is increasing, and the requirements for management flexibility are increasing. The main guideline and measure of the success of the functioning of enterprises is the volume of profit.Science has developed various approaches to solving the problems of cost reduction, however, under the current economic crisis conditions, the use of many of them is restrained by the need to make significant investments. Therefore, the search for low-investment ways to increase the efficiency of the use of costs is extremely relevant.
Keywords: state; costs; industrial enterprises